PENGUJIAN BLACK BOX TESTING PADA MULTIMEDIA INTERAKTIF BERBASIS WEBSITE TECHEDU - Isward Ajsam Azimi; Dian Rinjani (Institut Pendidikan Tapanuli Selatan, 2024)
Learning media is currently developing along with the times and technology. In Information and Communication Technology subjects, a book is often used as a medium, which allows students to simply view text and pictures. This study aims to test website-based interactive multimedia applications that present games with explanations, so that learning is more fun for students and two-way communication is established. The application system interface test is carried out using a questionnaire and a black box to ensure that the program functions properly. According to the test results based on the information collected through the questionnaire, this website-based application functions 100% as it should and the system is error-free. Of the 4 vocational high school students who participated in the questionnaire regarding this application, they expressed a strong preference for the TECHEDU application as a learning medium.